Effect of post-treatments on microstructure and mechanical properties of a novel nickel-based powder metallurgy superalloy processed by selective laser melting. (13th September 2019) - Hao, Zhibo; Tian, Tian; Yang, Yan; Peng, Shiqing; Li, Xinggang; Ge, Changchun; Gan, Bin; Zhu, Qiang
Abstract: A newly developed third generation nickel-based powder metallurgy (PM) superalloy, designated as FGH100L, was produced through Selective Laser Melting (SLM). Post-treatments, including Heat Treatment (HT), Hot Isostatic Pressing (HIP) and combined HIP + HT treatment, were carried out on the as-SLMed alloy to improve its mechanical properties by controlling the microstructure and/or reducing the defects in the alloy. Both HT and HIP treatments facilitated the recovery and recrystallization of the superalloy, especially when the solution temperature reached 1150 °C, thereby homogenizing the microstructure and refining the grains. During the post-treatment, the number density of γ ′ precipitates increased obviously with the process varying from SLM, SLM + HIP, SLM + HT to SLM + HIP + HT, and both yield strength and ultimate strength increased accordingly, indicating that the precipitation strengthening played a major role in improving the alloy strength. During the HIP process, the size and quantity of the pores were greatly reduced, which contributed greatly to a much higher elongation of the SLM + HIP alloy than that of the SLM and SLM + HT alloys. The fracture surfaces of the SLM alloys after different post-treatments showed transgranular fracture features, while the intergranular fracture was the main fracture mode of the as-SLM alloy.